Social network enterprise behaviors and patterns in SMEs: Lessons from a Portuguese local community centered around the tourism industry. (February 2016) - Fernandes, Silvia; Belo, Ana; Castela, Guilherme
Abstract: This study analyzes uses of social networks by small and medium-sized enterprises (SMEs) at the Algarve region in Portugal. Results suggest that some firms have integrated their business strategies with social networks, and have groups of professionals responsible for these platforms. Most managers perceive that social networks enhance business performance, but few measure the results. Firms that most frequently use social networks have managers with higher qualifications. This study identified two types of social-network use: a) product–client interaction and knowledge/(re)search, and b) marketing potential. A complementary analysis (cluster analysis) identified three behavioral patterns with varying involvement with social networks. These patterns relate with types of use, suggesting a level of social media involvement/performance. Enhancing performance is likely related to knowledge-oriented social networks. This study also suggests an approach for measuring the gap between types of social network use-behavioral/performance patterns and the reality in successful firms, which would be useful to apply or transfer to other firms and communities. Highlights: Firms need to know the existing types of social networks to take full advantage. A behavioral/performance approach is derived for social media strategic positioning. Results from business involvement in social networks are not generally measured. Training and control are important at workplace for avoiding productivity losses. Enhancing performance is likely related to knowledge-oriented social networks.